2021
DOI: 10.1080/17518423.2021.1886189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Home-based Bimanual Training in Children with Unilateral Cerebral Palsy (The COAD-study): A Case Series

Abstract: Purpose: To explore the child-and parent-related effects of home-based bimanual training in children with unilateral cerebral palsy. Methods: Case series of 14 children (2-7 years) who completed goal-oriented task-specific training for 3.5 hours/ week for 12 weeks by a program adopting implicit (n = 5) or explicit (n = 9) motor learning. A therapist and remedial educationalist coached parents. Progression on bimanual goals (Canadian Occupational Performance Measure (COPM)) and therapy-related parental stress (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…During the video calls, some families only reported some fatigue in children when performing the therapy. Other studies also found no adverse events in MT or home-based programs for children with US CP [28,36,38].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…During the video calls, some families only reported some fatigue in children when performing the therapy. Other studies also found no adverse events in MT or home-based programs for children with US CP [28,36,38].…”
Section: Discussionmentioning
confidence: 92%
“…Other studies with different home-based interventions used other ways to coach families. Some of them used webcam-monitoring during the performance of the intervention [ 60 ], while others maintained weekly phone calls and home visits [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemiparesis is defined as unilateral motor disability resulting from brain injury, wherein one side of the body is more significantly affected than the other (3). In hemiparetic CP, the upper extremities may suffer more severe impairments than the lower parts (4). Such upper limb disorders can significantly limit a child's ability to engage in daily activities and lead a normal life (5).…”
Section: Introductionmentioning
confidence: 99%